Mathematical Model for Transmission Dynamics of HIV/ADS and HSV-II Co-infection - Gurmu, Eshetu Dadi; Bole, Boka Kumsa; Koya, Purnachandra Rao (Applications of Modelling and Simulation, 2020)
In this paper, a mathematical model of HIV/AID and HSV-II co-infection has been formulated and analyzed. The main aim of this study was to give awareness for the community on the transmission dynamics of the disease. The well possedness of the formulated model equations was proved and the equilibrium points of the model have been identified. Qualitative analysis of the formulated model was established using basic reproduction number. The results show that the disease free equilibrium is locally asymptotically stable if the basic reproduction is less than one. The endemic equilibrium of the model equations are considered to exist when the basic reproduction number for each disease is greater than one. Finally, numerical simulations of the model equations are carried out using the software MATLAB R2015b with ODE45 solver. Numerical simulations illustrated that as we increase force of infection, the infections increases.